1965
DOI: 10.1136/bmj.2.5471.1156
|View full text |Cite
|
Sign up to set email alerts
|

Acute nephritis and streptococcal sore throat: a prospective study in general practice.

Abstract: The evidence linking acute nephritis and infection of the throat or skin with certain types of group A beta-haemolytic streptococci is of three kinds: (1) studies of streptococcal disease when acute nephritis was more prevalent than usual, (2) cultures from the throats of established cases of acute nephritis, and (3) serological studies of such cases for type-specific antibodies.Examples of the first are the reports of Manser and Wilson (1952), Reed (1953), Kleinman (1954), Seigel et al. (1955), Stetson et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

1971
1971
1996
1996

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…Laboratories which gave comparable results were London (95-7%'), Prague (97-90o), Copenhagen (97.30°), Jerusalem (99-8o0), Atlanta (97.00o), and Moscow (98-00%). Similar figures were also produced by Zanen et al (1959), Mitchell (1962, and Higgins et al (1965).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Laboratories which gave comparable results were London (95-7%'), Prague (97-90o), Copenhagen (97.30°), Jerusalem (99-8o0), Atlanta (97.00o), and Moscow (98-00%). Similar figures were also produced by Zanen et al (1959), Mitchell (1962, and Higgins et al (1965).…”
Section: Discussionsupporting
confidence: 75%
“…In the study of Higgins et al (1965), in which there were similarities to the present one in technique and in the population studied, the isolation rate for viruses was 2480°', which was higher than that of the present study. Respiratory syncytial virus was isolated in their study but not in the present one and this accounts for part of the difference.…”
Section: Discussioncontrasting
confidence: 74%
“…For a period of 12 months up to mid-December 1965 all patients of mine with acute infections of the upper respiratory tract were recruited into a study of transient urinary abnormalities following acute sore throat [1]. This paper reports the epidemiological findings, supplemented by data recorded in 1963 and 1964 and the results of a study of acute sore throat in all patients of the practice in 1959 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in that practice in 1958 and 1959 suggested that either 'nephritogenicity', if it existed, was not a sufficient cause of nephritis [6,7] or that only a very small proportion of patients yielding nephritogenic streptococci had streptococcal infection. In 1963 an unusual cluster of post streptococcal conditions occurred amongst my patients at a time when both streptococcal infections and infectious mononucleosis-like illnesses were prevalent [8] and at the end of that year a patient developed acute nephritis following a sore throat due to group A streptococci and a primary infection with herpes simplex virus [9].…”
Section: Introductionmentioning
confidence: 99%
“…The full picture of acute nephritis is not often encountered in general practice but urinary abnormalities without other signs of nephritis after acute streptococcal sore throat are relatively common [7,10,11]. Such abnormalities may be found in contacts of patients with acute nephritis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%